Non-coding RNAs in Nervous System Development and Disease - Salvatori, Beatrice; Biscarini, Silvia; Morlando, Mariangela (Frontiers in Cell and Developmental Biology, 2020)
The rapid advance of RNA sequencing technologies contributed to a deep understanding of transcriptome composition and has allowed the discovery of a large number of non-coding RNAs (ncRNAs). The ability of these RNA molecules to be engaged in intricate and dynamic interactions with proteins and nucleic acids led to a great expansion of gene expression regulation mechanisms. By this matter, ncRNAs contribute to the increase in regulatory complexity that becomes highly specific between tissues and cell types. Among the ncRNAs, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are especially abundant in nervous system and have been shown to be implicated in its development, plasticity and aging as well as in neurological disorders. This review provides an overview of how these two diverse classes of ncRNAs control cellular processes during nervous system development, physiology and disease conditions with particular emphasis on neurodegenerative disorders. The use of ncRNAs as biomarkers, tools or targets for therapeutic intervention in neurodegeneration are also discussed.